PERAN KUALITAS KARYAWAN DALAM PELAKSANAAN TATA KELOLA PEMELIHARAAN DAN OPTIMASLISASI PEMANFAATAN ASET (STUDI KASUS DI RUMAH SAKIT ISLAM JAKARTA CEMPAKA PUTIH) - Papan Gunadi; Rony Edward Utama (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
Optimizing asset utilization is a strategic component of hospital management, as it directly influences operational efficiency and service quality. The effectiveness of asset management is determined not only by the availability of asset management systems but also by the quality of employees involved in planning, maintenance, documentation, and supervision. This study aims to analyze the role of employee quality in the implementation of asset maintenance governance and the optimization of asset utilization at RSI Jakarta Cempaka Putih. The research employs a qualitative approach with a case study design, involving key informants from management, supporting units, technicians, and asset users. Data were collected through in-depth interviews, observations, and document reviews, and analyzed using Braun Clarke’s (2006) thematic analysis method.The study concludes that employee quality is a dominant factor linking effective asset maintenance to optimized asset utilization. These findings underscore the importance of strengthening human resource competence through technical training, certification, performance evaluation, and digitalization of asset management to support the sustainability of hospital operations. This research is expected to serve as a foundation for developing more comprehensive, employee-based asset management policies and strategies within RSI Jakarta Cempaka Putih.Keywords : Employee Quality, Asset Management, Asset Maintenance, Asset Optimization, Hospital, RSI Jakarta Cempaka Putih.